Inflammation and Cancer - Takuji Tanaka (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Based on the most recent clinical and epidemiologic information, one out of seven newly diagnosed epithelial malignancies worldwide result from infection and chronic inflammation in conjunction with cancer. This book draws contributions from international expert researchers from diverse disciplines, who addressed various aspects of experimental and clinical cancer biology, by selectively focusing on inflammation-mediated oncogenesis to debate these and related issues. Topics covered include the epidemiological links between cancer and inflammation, the parallels between inflammation and cancer, the role of inflammation in cancer, inflammatory genes as risk factors for cancer initiation and progression, inflammation and cancer angiogenesis, and preventative/therapeutic strategies. This comprehensive and cutting-edge Special Issue "Inflammation and Cancer" promises to serve as a vital guide and resource for investigators and clinicians working toward the goal of fighting the estimated 2200 inflammation-related oncogenesis fatalities occurring every day.